Education as a Tool for the Economic Integration of Migrants - Maria De Paola; Giorgio Brunello (Institute for the Study of Labor (IZA), 2016)
We examine the role of education in fostering the economic integration of immigrants. Although immigrants in Europe are – on average – slightly less educated than native individuals, there is a large heterogeneity across countries. We discuss evidence on student performance in international tests showing that children with an immigrant background display worse results than natives. While in some countries, such as Denmark and France, this gap is almost entirely explained by differences in socio-economic background, in others (Finland, Austria, Belgium and Portugal) the factors driving the gap are more complex and have roots also outside socio-economic conditions. We investigate how educational policies in the host count can affect the educational outcomes of immigrants. We focus our attention on pre-school attendance, school tracking, the combination of students and teacher characteristics, and class composition.
Keywords: I20; I21; I28; J24; J61; 330; education; immigration; European migration policies; school tracking; class composition